Pengaruh Pembelajaran Daring Terhadap Minat dan Prestasi Belajar Matematika Siswa Kelas X SMA Negeri 1 Gu - Herlawan Herlawan; Dian Lestari; Astia Ningsih (Jurnal Akademik Pendidikan Matematika, 2021)
The purpose of this research was to determine the effect of online learning on the interest in learning mathematics of SMA Negeri 1 Gu students. This research was a quantitative research using the Ex-post Facto method, where the research population was all students of class X SMA Negeri 1 Gu with a total of 248 students spread over 8 classes. The sampel used in this research was 25% of the population as many as 62 students. The instrument was questionnaire, this data was analyzed using simple linear regression analysis. The data of this study were obtained based on the results of inferential analysis by looking at the normality test, a significant value was obtained of 0.200> 0.05, the linearity test obtained a significant value of 0.283> 0.05, the autocorrelation test by looking at the dw value of 1.433 < du i.e. 1.6561 and less of (4 – du) 4 – 1.6561 and the heteroscedasticity test obtained a significant value of 0.586> 0.05. So it can be said that the data is normally distributed, linear, there are symptoms of autocorrelation and there are no symptoms of heteroscedasticity. By using simple linear regression the equation is obtained: Y = 28.922 + 0.727x. While the calculated F value obtained is 42.476 with a significant value of 0.00 <0.05. This shows that H0 is accepted, meaning that there is an effect of online learning on the interest in learning mathematics in X grade at SMA Negeri 1 Gu.